Seismic evaluation of offshore wind turbine by geotechnical centrifuge test - Seong, Jun‐Tae; Kim, Dong‐soo (Wind energy (Chichester, England), 2019)
As offshore wind turbines are now planned to be installed at seismic activity areas around Asia in large numbers, understanding of the seismic behavior of offshore wind turbine has become essential to evade structural hazards due to earthquake. Although the seismic behavior of the structure is largely affected by soil‐foundation‐structure interaction (SFSI), there is only a few experimental data about this subject as conventional offshore wind turbines are mostly located in the area where earthquakes are scarce. Geotechnical centrifuge experiment can provide reliable experimental data for this subject as it can reproduce field stress condition of the soil and simulate earthquake motion in a scaled model test. In this research, three case studies using centrifuge model test were performed to evaluate the seismic behavior of offshore wind turbine during the earthquake and permanent deformation after the earthquake. The results were compared with conventional seismic evaluation methods. Monopile, Monopod, and Tripod foundations were chosen for the experiment. Peak acceleration and rotational displacement of the wind turbine for three cases were evaluated under various intensities of seismic loading applied by centrifuge‐mounted shaking table. Results were compared with conventional evaluation method for design acceleration and conventional rotational displacement criteria suggested in DNV‐OS‐J101.